KAJIAN PENEMPATAN HELICOPTER STAND DI BANDAR UDARA INTERNASIONAL JENDERAL AHMAD YANI SEMARANG - Willy Ari Prasetya; Sundoro; Budi Prasetyo (Politeknik Penerbangan Indonesia Curug, 2020)
Arrangements for Helicopters in Aprons and the availability of adequate facilities is one of the supporting factors in providing the best service. In its implementation, during conducting research at the General Ahmad Yani International Airport Semarang, the author saw the conditions at the Parking Stand N1 in the Apron still not in accordance with their functions and uses. The unavailability of a helicopter stand to place a helicopter so that the helicopter placement process is still tandemed in the Parking Stand for Fix Wings and the unavailability of the helicopter stand markers has an impact on Marshallers who do not know the helicopter placement limit, do not have calculations that will also impact on objects around the Parking Stand . The problems that occur this of course causes not well ordered Helicopter parked tandem with a fix wing. The unavailability of Helipad or Helicopter Stand is less than optimal, so that it greatly affects the security and safety of airport service users